2019
DOI: 10.1111/1440-1681.13101
|View full text |Cite
|
Sign up to set email alerts
|

OBG‐like ATPase 1 inhibition attenuates angiotensin II‐induced hypertrophic response in human ventricular myocytes via GSK‐3beta/beta‐catenin signalling

Abstract: Obg‐like ATPase 1 (OLA1) that possesses both GTP and ATP hydrolyzing activities has been shown to be involved in translational regulation of cancer cell growth and survival. Also, GSK3β signalling has been implicated in cardiac development and disease. However, the role of OLA1 in pathological cardiac hypertrophy is unknown. We sought to understand the mechanism by which OLA1 regulates GSK3β‐β‐Catenin signalling and its functional significance in angiotensin‐II (ANG II)‐induced cardiac hypertrophic response. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…5 B). Our previous study showed that OLA1 directly interacted with GSK3β and inhibited its activity [ 21 , 22 ], which is also proved by other study [ 23 , 24 ]. Meanwhile, GSK3β can phosphorylate HIF1α and facilitate its degradation [ 25 ], which can explain why HIF1α decreased in OLA1-KO CRC cell lines.…”
Section: Resultssupporting
confidence: 68%
“…5 B). Our previous study showed that OLA1 directly interacted with GSK3β and inhibited its activity [ 21 , 22 ], which is also proved by other study [ 23 , 24 ]. Meanwhile, GSK3β can phosphorylate HIF1α and facilitate its degradation [ 25 ], which can explain why HIF1α decreased in OLA1-KO CRC cell lines.…”
Section: Resultssupporting
confidence: 68%
“…GSK-3 β has been shown to play vital roles in various biological processes and has shown to be a downstream mediator for Ang II. Narasimhan et al reported that inhibiting OBG-like ATPase alleviated the Ang II/GSK-3 β -induced hypertrophic response [ 30 , 52 ]. In addition, Ang II-mediated GSK-3 β signaling promoted muscle waste [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSK-3 β /mTOR signaling has been shown to regulate autophagy [ 28 ], but inhibition of GSK-3 β /mTOR could induce synaptogenesis and axonal repair in a neonatal rat model of HIE [ 29 ]. It was suggested that GSK-3 β was a downstream target for Ang II [ 30 ]. However, it remains unclear whether Ang II regulates GSK-3 β /mTOR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen synthase kinase-3β (GSK3β) is a serine-threonine kinase, which involves in some cellular signaling pathways 22. GSK3β signaling has been implicated in cardiac disease and human cancers 23. However, little is known about the role of GSK3β in spermiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that male hypogonadism was associated with microRNAs (miRNAs) 24. Evidences indicated that microRNA-26a (miR-26a) plays important roles in tumor cells and neural stem cells; however, the function of miR-26a during male hypogonadism remains unclear 23,25. Although previous studies have reported that Rg3 had multiple pharmacological functions, the mechanisms by which Rg3 regulates the proliferation and apoptosis in MLTC-1 cells against TP remain unclear.…”
Section: Introductionmentioning
confidence: 99%